Improving Estimation of Submarine Groundwater Discharge Using Radium and Radon Tracers: Application in Jiaozhou Bay, China. Issue 10 (30th October 2017) - Zhang, Yan; Li, Hailong; Xiao, Kai; Wang, Xuejing; Lu, Xiaoting; Zhang, Meng; An, An; Qu, Wenjing; Wan, Li; Zheng, Chunmiao; Wang, Xusheng; Jiang, Xiaowei
Abstract: Radium and radon mass balance models have been widely used to quantify submarine groundwater discharge (SGD) in the coastal areas. However, the losses of radium or radon in seawater caused by recirculated saline groundwater discharge (RSGD) are ignored in most of the previous studies for tracer‐based models and this can lead to an underestimation of SGD. Here we present an improved method which considers the losses of tracers caused by RSGD to enhance accuracy in estimating SGD and SGD‐associated material loadings. Theoretical analysis indicates that neglecting the losses of tracers induced by RSGD would underestimate the SGD by a percentage approximately equaling the tracer activity ratio of nearshore seawater to groundwater. The data analysis of previous typical case studies shows that the existing old models underestimated the SGD by 1.9–93%, with an average of 32.2%. The method is applied in Jiaozhou Bay (JZB), North China, which is experiencing significant environmental pollution. The SGD flux into JZB estimated by the improved method is ∼1.44 and 1.34 times of that estimated by the old method for 226 Ra mass balance model and 228 Ra mass balance model, respectively. Both SGD and RSGD fluxes are significantly higher than the discharge rate of Dagu River (the largest one running into JZB). The fluxes of nutrients and metals through SGD are comparable to or even higher than those from local rivers, which indicates that SGD is an important source of chemicals into JZB and has important impact on marine ecological system. Key Points: Improving estimation of submarine groundwater discharge (SGD) by considering losses of tracers caused by recirculated seawater The data analysis from some typical case studies confirms the significance of the model improvement in SGD estimation SGD‐driven nutrient and metal fluxes in Jiaozhou Bay are significantly higher than those from local rivers